Introduction to Special Issue: Belt and Road Initiative – 10 Years on - Kerry Brown; Sinan Chu (Journal of Current Chinese Affairs)
It has been over a decade since the emergence of what is now best known as the “Belt and Road Initiative” (BRI). This Special Issue, a decade after the BRI was launched, highlights the immense complexity not only of the idea itself but also of China's global influence and the varied attitudes and responses towards it. We hope that these studies, with their diverse approaches and evidence bases, contribute to enriching the expanding literature on the BRI – a trend that is unlikely to wane anytime soon as China continues to be a major global force in the twenty-first century.